Improving Students’ Narrative Writing Quality through Structured Visual Mapping: A Quasi-Experimental Study - Rukmana Fachrul Islam; Armisari Armisari; Natalia Manuhutu (Hasanuddin University, 2025)
This study examines the effectiveness of Structured Visual Mapping as a prewriting strategy to enhance the narrative writing quality of senior high school EFL learners in Indonesia. Many students face challenges in developing ideas, organizing narrative elements, and applying appropriate vocabulary and grammar when composing narrative texts. Using a quasi-experimental design, 60 eleventh-grade students from SMA Negeri 1 Marioriwawo were divided into an experimental group taught using Structured Visual Mapping and a control group taught through conventional instruction. Pretests and posttests were administered, and students’ writing performance was assessed using the ESL Composition Profile. The results show that the experimental group achieved significantly higher improvement across all five writing components, with a mean gain of 9.3 compared to 1.9 in the control group. The posttest t-test value (t = 2.024 > 2.000) confirmed that the intervention had a significant effect on students’ writing performance. These findings indicate that Structured Visual Mapping effectively supports students in generating ideas, sequencing narrative structure, and improving lexical and grammatical accuracy. This study recommends integrating Structured Visual Mapping into narrative writing instruction and suggests further exploration of its application in other writing genres or digital learning contexts.